EKSISTENSI PENDIDIKAN AGAMA ISLAM DI DESA NGEPEH KECAMATAN TUGU KABUPATEN TRENGGALEK: Studi Pengabdian Pada Masyarakat dalam Pembentukan Karakter Berkolaborasi dengan Satgas Covid-19 - Mukhammad Abdullah; Ahmad Fahrur Rhozi Alansori (CV. Adiguna Kertosari, 2021)
Education is the best curriculum to apply knowledge, culture and science. As for realizing all these goals, we need the right idea. The measure of success for character education is not only about values ​​but it is hoped that someone can apply it in their social life. For that, someone who acts as an agent of change must apply the right method. Character education is one of the main goals of education in Indonesia. The community must be capable of actualizing their knowledge in real life. Such a statement must be realized with the role of the community to cultivate which strategies and methods are appropriate to build character. Therefore, there is a need for special research related to how character can be formed. One of them is the existence of Islamic Religious Education. The purpose of this study was to find out how the nature of Islamic Religious Education in its actualization in the social life of the Ngepeh Village community. The research in this service is a qualitative research with a field research approach. The subjects studied were TPQ Baitul Qadar, TPQ Ponggok, tutoring, and the community who collaborated with the Covid-19 task force. The results of this study found that there was a significant positive character formation in the three subjects studied, namely changes in the character of students in tutoring, santri and female students at TPQ Ponggok and TPQ Baitul Qadar, as well as the level of character that was considered positive by the community who collaborated with the COVID-19 task force. 19. The expected results of this research can be a contribution and open up dialectics as a solution to the decline in character, especially during the pandemic.